Personalized medicine for asthma in tropical regions. Issue 3 (June 2020) - Caraballo, Luis; Acevedo, Nathalie; Zakzuk, Josefina
Abstract : Purpose of review: Precision medicine could help to improve diagnosis and treatment of asthma; however, in the tropics there are special conditions to be considered for applying this strategy. In this review, we analyze recent advances of precision allergology in tropical regions, highlighting its limitations and needs in high-admixed populations living under environments with high exposure to house dust mites and helminth infections. Recent findings: Advances have been made regarding the genetic characterization of the great diversity of populations living in the tropics. Genes involved in shared biological pathways between immune responses to nematodes and the allergic responses suggested new mechanisms of predisposition. Genome wide association studies of asthma are progressively focusing on some highly replicated genes such as those in chromosome 17q31-13, which have been also replicated in African ancestry populations. Some diagnostic difficulties, because of the endemicity of helminth infections, are now more evident in the context of phenotype definition. Summary: The clinical impact of the advances in precision medicine for asthma in the tropics is still limited and mainly related to component resolved diagnosis. More basic and clinical research is needed to identify genetic, epigenetic, or other biologic markers that allow and accurate definition of phenotypes and endotypes of this heterogeneous disease. This will substantially improve the selection of personalized treatments.